ClickMD: an intuitive web-oriented molecular dynamics platform. (June 2011) - Cristiani, Andrea; Brisotto, Nicola; Cedrati, Fabian Chatwin; Floris, Matteo; Scapozza, Leonardo; Moro, Stefano
Background: Molecular dynamics (MD) simulations are broadly used to reproduce protein motions at an atomic level of detail. Running MD simulations is generally considered an expert-driven task.Discussion: ClickMD provides an integrated web-oriented platform for processing and analyzing the time-dependent behavior of a biomolecular system in an MD workflow. ClickMD is freely available online and can be easily integrated into the drug-design process, in particular in combination with molecular docking simulations.Conclusion: ClickMD has the potential to reduce the shuffling among various software applications and to facilitate the seamless processing of the MD trajectories.